One track mind - Robertson, S. (Victoria University, 2021)
01. AI in Sport - Help or Hindrance? 02. Will Your Job Exist in the Future? 03. Can Sport Ever Be Fair? 04. Is Technology Ruining the Athlete-Coach Relationship? 05. Where Will Sport Be in 20 Years? 06. Should Sport Contribute to Society?